In vitro effects of platelet-derived factors of brain glioma patients on C6 glioma cells - L. D. Liubich; N. I. Lisyanyi; T. A. Malysheva; L. P. Staino; D. M. Egorova; V. V. Vaslovych (Regulatory Mechanisms in Biosystems, 2019)
Platelets play an important part in the progression and pathological angiogenesis of brain glioma because of the different granules content and release of microvesicles that are the source of numerous mediators and bioactive substances, which probably provides a "strategy" for the tumour survival. The objective of study was exploring the effect of platelet-released secretion products of patients with brain glioma on the experimental model of tumour growth in vitro. For this purpose, the cells of glioma C6 were cultured for 72 hours under the addition of modified media containing platelet-released secretion products or conditioned media of peripheral blood cells of patients with glioma as well as persons of the comparison group without rough somatic pathology. In control glioma C6 cultures in standard conditions cell clusters were formed by the type of "spheroids", from which radial cell migration occurred, a tense cellular or reticular growth zone was formed, and tumour cells preserved their ability to mitotic division. Under the influence of platelet-released secretion products of patients with glioma, differently directed effects on cell mitotic activity and the number of cell clusters in glioma C6 cultures were detected depending on the degree of tumour malignancy: stimulating effect under the influence of platelet factors of patients with high-malignancy glioma (G4) and inhibitory effect – due to the influence of platelet factors of patients with differentiated glioma (G2). In contrast to the thrombocyte-released factors, the conditioned media of a common pool of peripheral blood cells of patients with G4 glioma suppressed the mitotic activity of tumour cells and did not affect the number of cell clusters. No changes in glioma C6 cultures were revealed after the influence of platelet-released secretion products of persons of the comparison group. The obtained data confirm the important role of platelets in the pathogenesis of brain glioma, pointing to the fundamental difference in the spectrum of biologically active molecules that are released by platelets of patients depending on the degree of tumour malignancy and are able to regulate the cell cycle and proliferative activity of the glioma tumour cells, which may have application as a diagnostic marker as well as predictive marker of response to antitumour therapy.